2022
DOI: 10.3390/nano12111886
|View full text |Cite
|
Sign up to set email alerts
|

Electric Transport in Few-Layer ReSe2 Transistors Modulated by Air Pressure and Light

Abstract: We report the fabrication and optoelectronic characterization of field-effect transistors (FETs) based on few-layer ReSe2. The devices show n-type conduction due to the Cr contacts that form low Schottky barriers with the ReSe2 nanosheet. We show that the optoelectronic performance of these FETs is strongly affected by air pressure, and it undergoes a dramatic increase in conductivity when the pressure is lowered below the atmospheric one. Surface-adsorbed oxygen and water molecules are very effective in dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…The transfer characteristics (I ds –V bg ) were studied at V ds = 0.2–1 V and are presented both in linear-, and log-scale as shown in Figure 2 a,b, respectively. A bias-dependent increase in on-current (I on ) has been observed on increasing V ds from 0.2 to 1 V which demonstrates usual ReSe 2 transistor characteristics, similar to work [ 22 , 44 ]. The field-effect mobility denoted as µ FE can be evaluated by the following relation: …”
Section: Resultssupporting
confidence: 74%
“…The transfer characteristics (I ds –V bg ) were studied at V ds = 0.2–1 V and are presented both in linear-, and log-scale as shown in Figure 2 a,b, respectively. A bias-dependent increase in on-current (I on ) has been observed on increasing V ds from 0.2 to 1 V which demonstrates usual ReSe 2 transistor characteristics, similar to work [ 22 , 44 ]. The field-effect mobility denoted as µ FE can be evaluated by the following relation: …”
Section: Resultssupporting
confidence: 74%
“…According to the eqs and , the carrier mobility of the heterojunction μ and τ tranit are estimated to be 0.904 cm 2 V –1 s –1 and 8.8 × 10 –8 s, respectively. The mobility is not that high, but it is typical or even better than that reported in exfoliated rhenium dichalcogenides, such as ReSe 2 (μ = 0.03 cm 2 V –1 s –1 ) . The gain G can be calculated to 9.09 × 10 6 .…”
Section: Resultsmentioning
confidence: 72%
“…The mobility is not that high, but it is typical or even better than that reported in exfoliated rhenium dichalcogenides, such as ReSe 2 (μ = 0.03 cm 2 V −1 s −1 ). 37 The gain G can be calculated to 9.09 × 10 6 . This is ascribed to the presence of the built-in electric field, which reduces the recombination of carriers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As we discussed in the above sections that NPC was widely observed in various types of materials. ,,,, Different origin has been proposed for NPC generation, which can be suitable for various kind of applications. The NPC effect has been used for the fabrication of humidity and light sensors, highly sensitive photodetectors, and nonvolatile memories. , Qin et al demonstrated that the NPC in nanodiamonds can be applied for humidity sensors with the sensitivity of 1.26 × 10 6 %, which is the highest in carbon-based humidity sensors . Zhuang et al showed the application of NPC in humidity sensors with a responsivity of 418.1 μAW –1 (at high humid RH = 90%) .…”
mentioning
confidence: 99%